1980
DOI: 10.1111/j.1432-1033.1980.tb04867.x
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Enzymes Involved in Amino‐Acid Metabolism in Developing Rat Placenta

Abstract: Aspartate transaminase, alanine transaminase, glutamate dehydrogenase, arginase, serine dehydratase, tyrosine transaminase, glutamine synthetase, glutaminase and adenylate deaminase activities were measured in crude homogenates of 12, 19 and 21-day rat placentae. There is a considerable quantitative importance in enzymes able to produce free ammonia, such as adenylate deaminase and glutamate dehydrogenase, activity that progressively decrease with the age of placenta. The glutamine synthetase and tyrosine tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…The mRNAs of SNAT3 were found to be expressed in Bewo cells Eadie-Hofstee plot analysis showed that glutamine uptake was two-phase uptake (high-affinity phase-0.13mM, low-affinity phase-1.4mM).We suggest that Km value of SNAT3 was similar to that of low affinity phase and SNAT3 transport glutamine in cytotrophoblast cells. In the rat placenta, the activity of glutamine synthetase is greatest on the 12 th day of gestation [40]. This corresponds to our finding that the expression level of SNAT3 in the placenta is the highest in the 11 th day of gestation.…”
Section: Discussionsupporting
confidence: 75%
“…The mRNAs of SNAT3 were found to be expressed in Bewo cells Eadie-Hofstee plot analysis showed that glutamine uptake was two-phase uptake (high-affinity phase-0.13mM, low-affinity phase-1.4mM).We suggest that Km value of SNAT3 was similar to that of low affinity phase and SNAT3 transport glutamine in cytotrophoblast cells. In the rat placenta, the activity of glutamine synthetase is greatest on the 12 th day of gestation [40]. This corresponds to our finding that the expression level of SNAT3 in the placenta is the highest in the 11 th day of gestation.…”
Section: Discussionsupporting
confidence: 75%
“…Recently we reported the ability of rat placenta to synthesize lactate from both D-glucose (31) and L-alanine (32). Production of placental lactate from L-alanine seems to be involved in the mechanism of the maternofetal transfer of the amino acid (32) and is consistent with the reported presence of alanine aminotransferase in rat placenta (16,33). The level of labeled lactate in fetal plasma after infusion through the maternal left uterine artery was much lower with [U-14C]-glycerol than with the other substrates studied.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that the developing placenta expresses SDH, particularly during the early stages of foetal development [10]. The specific activity of SDH in extracts prepared from the placenta at d19 of gestation was 0.34 ± 0.05 nmol/min/mg protein, or approximately 26% of the specific activity found in the maternal liver at the same stage of gestation.…”
Section: Resultsmentioning
confidence: 90%